Ambientes familiares tóxicos : impactos da violência conjugal na vinculação entre mães e filhos, no reconhecimento de emoções e nos níveis de cortisol - Boeckel, Mariana Gonçalves (2013)
OBJECTIVE: To identify the reverberation of IPV on the emotional recognition process and cortisol levels of mothers and children, as well as on the maternal bond and emotional dysregulation of the mothers. METHOD: This thesis consists of five studies. The first study presented the adaptation and factor analysis of the Inventory of Perceived Maternal Attachment (IPVM), an instrument that assesses the maternal emotion bond. The second was a result of the Programa Institucional de Bolsas de Doutorado Sanduíche no Exterior PDSE - CAPES, and aimed to evaluate the relation between the mental health status of abused women, their partners violence toward the children and their maternal behavior. The third study investigated the impact that IPV and difficulties in emotional dysregulation have on maternal bond quality among women victims of IPV. The fourth study purposed to understand the impact of IPV on the ability to recognize facial expressions of emotion in women victims and their children. Finally, the last study investigated the chronic cortisol concentrations, measured through hair samples in women victims of sexual violence and their children. RESULTS: In the first study, exploratory factor analysis indicated the presence of two factors semantically congruent and complementary: interaction/affection and maternal perception. The second study highlighted the occurrence of IPV as a factor recrudescent for the probability of violence against the children of women victims of IPV, and the protective behaviors of mothers to children when facing the aggressive acts of their partners toward children shown to be associated with the mother s mental health. The third study found negative correlations between maternal bond quality and: IPV (physical, psychological or sexual violence), symptoms of posttraumatic stress disorder in children and difficulties in emotional regulation in mothers. The fourth study demonstrated that children exposed to marital violence had a greater bias to identify the emotion anger and fear in neutral faces, and mother s victims of IPV showed greater bias to fear. The fifth study unveiled that the cortisol levels of mothers victims of sexual violence and their children were higher than those of controls. CONCLUSION: The present thesis brings unprecedent results in the scientific literature. The studies presented here highlight the interpersonal, emotional, cognitive and biological impacts of IPV on women and their children. Given that violence is a complex phenomenon, it seems important to underline the significance of further studies on IPV and its reverberations beyond female victims, including the family system.